Pengaruh Perceived Organizational Support terhadap Readiness for Change pada Guru - Fadillah Putri Amalia Rizky; Dinda Dwarawati (Bandung Conference Series: Psychology Science, 2023)
Abstract. Organizational change is something that cannot be avoided to achieve success in the competitive world of work, continuity and existence of the organization. An important factor in the success of an organization to make changes is individual readiness to change (readiness for change). Readiness for change is the extent to which individuals cognitively and emotionally have the desire to accept, embrace and adapt a change plan. Employee readiness to face change will have a positive orientation towards the organization when it has perceived organizational support. This study aims to see how much influence perceived organizational support has on readiness for change in 90 public high school teachers in Cianjur District. The measuring tool used is the Survey of Perceived Organizational Support (SPOS) which refers to the theory of Eisenberger et al. (1986) and the readiness for organizational change scale which refers to the theory of Holt et al., (2007). The sampling technique used is saturated sampling. The method used is causality quantitative method with simple linear regression analysis technique. The results of this study indicate that perceived organizational support has a significant effect on readiness for change by 77.1% Abstrak. Perubahan organisasi merupakan hal yang tidak dapat dihindari untuk mencapai keberhasilan dalam persaingan dunia kerja, kelangsungan serta eksistensi organisasi. Faktor penting dalam keberhasilan organisasi untuk melakukan perubahan yaitu kesiapan individu untuk berubah (readiness for change). Readiness for change adalah sejauh mana individu secara kognitif dan emosional memiliki keinginan untuk menerima, merangkul dan mengadaptasi rencana perubahan. Kesiapan karyawan menghadapi perubahan akan memiliki orientasi positif terhadap organisasi ketika memiliki perceived organizational support. Penelitian ini bertujuan untuk melihat seberapa besar pengaruh perceived organizational support terhadap readiness for change pada 90 guru SMA Negeri di Kecamatan Cianjur. Alat ukur yang digunakan yaitu Survey of Perceived Organizational Support (SPOS) yang mengacu pada teori Eisenberger et al. (1986) dan readiness for organizational change scale yang mengacu pada teori Holt et al., (2007). Teknik sampling yang digunakan adalah sampling jenuh. Metode yang digunakan yaitu metode kuantitatif kausalitas dengan teknik analisis regresi linier sederhana. Hasil penelitian ini menunjukkan bahwa perceived organizational support berpengaruh signifikan terhadap readiness for change sebesar 77.1%.